Association of upstream clopidogrel administration and myocardial reperfusion assessed by cardiac magnetic resonance imaging in patients with ST-elevation myocardial infarction. Issue 2 (June 2014) - de Waha, Suzanne; Eitel, Ingo; Desch, Steffen; Fuernau, Georg; Lurz, Philipp; Schuler, Gerhard; Thiele, Holger
Background: Current ST-elevation myocardial infarction (STEMI) guidelines recommend initiation of clopidogrel treatment as early as possible before angiography, based on pharmacokinetic and positive registry data. However, the mechanisms of the beneficial effect of clopidogrel pretreatment are unclear. Aim of this study was to investigate the impact of upstream clopidogrel on infarct size and microvascular obstruction (MO) assessed by cardiac magnetic resonance imaging (CMR) in STEMI patients. Methods: STEMI patients reperfused by primary angioplasty ( n =423) <12 h after symptom onset underwent CMR 3 days (IQR 2-4) after the index event. Infarct size and MO were measured 15 min after gadolinium injection as percentage of left ventricular mass (%LV). Clopidogrel administration (loading dose pre or post catheterisation laboratory arrival) was recorded. Results: A total of 19.9% ( n =84) of patients received clopidogrel prior to catheterisation laboratory arrival. Infarct size did not differ significantly in patients with versus those without upstream clopidogrel treatment (17.0%LV [IQR 6.3-25.1] vs. 17.9%LV [IQR 8.7-28.8]; p =0.13). In contrast, the prevalence and extent of MO were significantly reduced in patients receiving upstream clopidogrel treatment (prevalence of MO: 57.8% vs. 73.8%; p =0.004/ extent of MO: 0.41%LV [IQR 0.00–0.90] vs. 0.80%LV [IQR 0.00–2.55]; p <0.001). After adjustment for baseline characteristics associated with the occurrence of MO, pretreatment with clopidogrel remained significantly associated with the absence of MO (OR 0.39, 95%CI 0.22–0.71; p =0.002). Conclusions: Upstream clopidogrel treatment prior to catheterisation laboratory arrival is associated with a significant decrease in the prevalence and extent of MO. A randomised trial is warranted to confirm these results.